2022
DOI: 10.1111/apt.16974
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Dietary management of coeliac disease

Abstract: To begin a discussion on the dietary management of coeliac disease (CD), a review of the multifaceted negative impact of the gluten-free diet (GFD) on the individual with CD needs to be described. The impact of diet and disease ranges from the cost of GF products, [1][2][3][4] to the limitations on an individuals' social life, [5][6][7] the impact on quality of life (QOL) and the nutritional concerns of the diet. [10][11][12] This chapter will explore the various issues confronting an individual with CD and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 69 publications
(250 reference statements)
0
10
0
Order By: Relevance
“…In assessing a gluten-free diet, this has been the gold standard. 7 Fourth, the optimal delivery of any diet requires good education, motivating technique and ongoing counselling together with access (email, telephone or personal) to the dietitian for queries.…”
Section: Letter: Dietitians Are More Than Coachesmentioning
confidence: 99%
“…In assessing a gluten-free diet, this has been the gold standard. 7 Fourth, the optimal delivery of any diet requires good education, motivating technique and ongoing counselling together with access (email, telephone or personal) to the dietitian for queries.…”
Section: Letter: Dietitians Are More Than Coachesmentioning
confidence: 99%
“…The only management currently recommended is lifetime adherence to a gluten-free diet, which improves symptom burden but brings about other challenges including impact on quality of life. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Timely identification, diagnosis and management of CD is therefore key. The only current management is lifetime adherence to a gluten free diet (GFD) which improves symptom burden but brings about other challenges (10).…”
Section: Introductionmentioning
confidence: 99%
“…Dietitians have an important role in helping people achieve GFD adherence. This is because they are trained to assess patient knowledge, dietary adherence, nutritional status and psychosocial needs; monitor laboratory results; and provide individualised dietary advice 8 . However, a recent survey completed by 158 dietetic departments in England that provided dietetic gastroenterology services identified that specialist dietetic CD clinics were not provided in 49% of these services, 9 suggesting that adequate dietetic support for patients living with CD may be lacking.…”
Section: Introductionmentioning
confidence: 99%